PSIKOLOGI SASTRA NOVEL REMAJA MY IDIOT BROTHER KARYA AGNES DAVONAR - Nofianti, Nira; Priyadi, A. Totok; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe purpose is describing to psychology of author, psychology of the main character, psychology of reader in the novel and the implementation in learning procces to Senior High School. Method of research use to method desription shaped qualitation with pschology behavioristic. Techniques in the research is techniques documentary studies and interview through social media with the data collection tool is researches themselves and data card. Pschology of aouthor realized with sad, can accept reality, suffering from a diases, family can?t to be continued education find in the text novel not much different with life of the aouthor. Pschology of main caharcter realized with the feeling of shy,annoyed, sad, angry, afraid, happy and guilty feeling. Pschology of reader the feel moved, touch of the heart and impressed already to read novels My Idiot Brother by Agnes Davonar . The research can to be as learning Indonesian languange in the Senior High School class of XII . The results is hoped used the teachers for teaching material in the school.Keywords:Psychology, Literature, Behavioristic